2015
DOI: 10.3109/03639045.2015.1054834
|View full text |Cite
|
Sign up to set email alerts
|

Stability of cefozopran hydrochloride in aqueous solutions

Abstract: The influence of pH on the stability of cefozopran hydrochloride (CZH) was investigated in the pH range of 0.44-13.00. Six degradation products were identified with a hybrid ESI-Q-TOF mass spectrometer. The degradation of CZH as a result of hydrolysis was a pseudo-first-order reaction. As general acid-base hydrolysis of CZH was not occurred in the solutions of hydrochloric acid, sodium hydroxide, acetate, borate and phosphate buffers, kobs = kpH because specific acid-base catalysis was observed. Specific acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Many studies have shown that the degradation of β-lactam ring is related to water. 8 9 The β-lactam ring could be affected by OH - and H + when it was exposed to water, resulting in the rupture of the amide bond on the quaternary ring. 10 The hydrolytic degradation mechanism of imipenem is related to the opening of the quaternary ring as shown in Scheme 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that the degradation of β-lactam ring is related to water. 8 9 The β-lactam ring could be affected by OH - and H + when it was exposed to water, resulting in the rupture of the amide bond on the quaternary ring. 10 The hydrolytic degradation mechanism of imipenem is related to the opening of the quaternary ring as shown in Scheme 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Only in a paper by Chen et al was it mentioned that the product of cephalexin hydrolysis was identified by LC/MS . A number of cephalosporins have been subjected to hydrolysis and the products have been analyzed by ESI‐MS . However, the identified products were degradation products and not hydrolysis products.…”
Section: Introductionmentioning
confidence: 99%
“…The strong activity to resist aerobic Gram-negative bacteria and anaerobic bacteria makes it a pharmacokinetic long-acting drug. Due to the side effects of β-lactams caused by the generation of degradation products, it is important to estimate the stability of cephems. …”
Section: Introductionmentioning
confidence: 99%